(untitled) (Research, Society and Development, 2020)
Introduction: Cardiac surgeries are described as complex interventions requiring adequate treatment in all surgical phases. General objective: to conduct a literature review to investigate the conduct of the nursing professional in the immediate postoperative period in heart transplantation. Methodology: for the development of this study, a literature review was conducted with a qualitative approach, opting only for publications with less than 5 years indexed in the journals in the health area. Result: the main complications that patients in the postoperative period by heart transplantation may face in their hospitalization time are, acute pain, impaired gas exchange, hypothermia, decreased cardiac output and risk for fluid volume desiquilibrium,cardiacrritia, hemodynamic instability, acute myocardial infarction. Pulmonary presentations may be atelectasis, pneumonia, episode of hypoxemia, and acute respiratory distress syndrome. Therefore, nurses are extremely important because the professional acts in hemodynamic evaluation, evaluation of renal function and water balance; prevention of infections; detection and treatment of rejection; and ensuring the adequate supply of nutrients, in addition to providing human and material resources. Being responsible for caring, controlling and observing the patient, taking into account the complexity of the surgery.